2008
DOI: 10.1007/s10902-008-9116-3
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Happiness in Later Life: An Investigation into the Role of Daily and Weekly Flow Experiences

Abstract: Happiness, Life satisfaction, Flow, Older adults, Aging,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 42 publications
3
47
0
9
Order By: Relevance
“…We can surmise from these results that flow can be experienced independent of gender, education level, or culture (Csikszentmihalyi, 1990), but the situations that may induce the experience can differ. Earlier results suggest the frequency and quality of optimal experiences may vary at the individual level (Collins, Sarkisian, & Winner, 2009). Studies about the effect of age on flow (Lawton, 1989) suggest that older adults may experience flow if the perceived challenges are slightly above the skills of the person.…”
Section: Discussionmentioning
confidence: 98%
“…We can surmise from these results that flow can be experienced independent of gender, education level, or culture (Csikszentmihalyi, 1990), but the situations that may induce the experience can differ. Earlier results suggest the frequency and quality of optimal experiences may vary at the individual level (Collins, Sarkisian, & Winner, 2009). Studies about the effect of age on flow (Lawton, 1989) suggest that older adults may experience flow if the perceived challenges are slightly above the skills of the person.…”
Section: Discussionmentioning
confidence: 98%
“…Due to these contradictory findings on People engaging in flow often report several typical features, such as the merging of action and awareness, a sense of control, and an altered sense of time [4]. However, people engaging in anxiety often feel a loss of control; Collins and colleagues found that higher flow was positively associated with higher arousal of positive affect (i.e., feeling fired-up, enthusiastic) and life satisfaction, while negatively associated with lower arousal of negative affect (i.e., feeling sad and disappointed) [21]. As many studies on flow were focused on its positive effect in young people [14,22], studies on the relation of flow to negative experiences such as anxiety are scarce in the existing literature.…”
Section: Flow and Self-esteemmentioning
confidence: 99%
“…Cela signifie que le partage d'activités en couple qui remplissent les conditions fondamentales de l'expérience flow -équilibre entre défi et habiletés, principalement -favorise l'expansion de soi et produit un affect positif qui contribue à améliorer la relation romantique. Ajoutons que cette relation entre flow et affect positif apparaît fréquemment : par exemple, chez des étudiants du premier cycle universitaire (Rogatko, 2009) et chez des personnes âgées (Collins, Sarkisian et Winner, 2009). Figure 3.…”
Section: Dans Le Domaine Du Travail Engeser Et Baumannunclassified